First Nations Australians’ self-determination in health and alcohol policy development: a Delphi study ... - Stearne, Annalee; Lee, Kylie; Allsop, S; Shakeshaft, A; Wright, M (La Trobe, 2024)
Background: Recognition of the role of structural, cultural, political and social determinants of health is increasing. A key principle of each of these is self-determination, and according to the United Nations (2007), this is a right of Indigenous Peoples. For First Nations Australians, opportunities to exercise this right appear to be limited. This paper explores First Nations Australian communities’ responses to reducing alcohol-related harms and improving the health and well-being of their communities, with a focus on understanding perceptions and experiences of their self-determination. It is noted that while including First Nations Australians in policies is not in and of itself self-determination, recognition of this right in the processes of developing health and alcohol policies is a critical element. This study aims to identify expert opinion on what is needed for First Nations Australians’ self-determination in the development of health- and alcohol-related policy. Methods: This study used the ...